POSITIONED BETWEEN CHINA AND RUSSIA: HE CENTRAL ASIAN COUNTRIES FIND THEIR OWN APPROACH TO PRIVATIZATION - GINSBURG, Veniamin; TROSCHKE, Manuella (CENTRAL ASIA AND THE CAUCASUS, 2005)
Even in developed Western states, economic transformation is a complex and usually rather painful process. What is more, complete economic transformation during transition to the market is accompanied by extremely strong social upheavals. The fifteen-year practice of re-forms in the post-Soviet countries has demonstrated so many diverse nuances that the need for a carefully elaborated individual approach to each problem in each republic and continuous adjustment of their transition strategies and tactics is crystal clear. One of the most difficult and controversial questions is the degree of the state’s participation in enterprise and economic development management during and after privatization. Debates are still going on between the supporters of the conceptions of a “strong” and a “weak” state. In different countries, both conceptions demonstrate several strong and weak aspects and the arguments of the participants in the debate are becoming broader, but there are still doubts about the specific benefit to be derived from implementing their proposals. However, these countries have already accumulated a fair amount of experience in economic transformation, the study and elucidation of which can promote a more rational solution to the problem as a whole.